ANALISIS KUALITAS AUDITOR INSPEKTORAT PROVINSI LAMPUNG - Yohannes P Kumagaya (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2016)
The purpose of this study is to see the effect of the competence and independence of theauditors on the quality of the results of the examination of Lampung Province Inspectorateemployees.The analytical method used is to use the method of qualitative data analysis, as it providesinformation based on the translation of the data in the form of sentences. These results indicate thatthe qualitative analysis of the results obtained the following description: average values over thevariables Competence respondents with a score of 3.37 for 67.48% real (good), the average value ofvariable independence responder above by 3 , 39 with a score of 67.78% real (good), the averagevalue of the response variable quality test results for 3.37 with a score of 67.45% real (good).